Molecular phylogeny of the large South American genus Eriosyce (Notocacteae, Cactaceae): Generic delimitation and proposed changes in infrageneric and species ranks. Issue 3 (28th August 2019) - Guerrero, Pablo C.; Walter, Helmut E.; Arroyo, Mary T.K.; Peña, Carol M.; Tamburrino, Italo; De Benedictis, Marta; Larridon, Isabel
Abstract :   Eriosyce is one of most species‐rich genera within Notocacteae (Cactaceae) harboring a variety of stem and flower morphologies, and fruits with basal abscission. The lack of a well‐sampled molecular phylogeny contributes to the current taxonomic instability of the genus, where its circumscription and infrageneric classification has been questioned. Specimens of Eriosyce (63 taxa) plus 19 outgroups were analyzed through sequencing three plastid noncoding introns ( rpl32‐trnL, trnL‐trnF, trnH‐psbA ), one plastid gene ( ycf1 ), and one nuclear gene ( PHYC ). Individual markers and concatenated matrices were analyzed using maximum likelihood and Bayesian approaches. Phylogenetic analyses strongly support the monophyly of Eriosyce s.l. Furthermore, seven clades within Eriosyce s.l. were defined based on supported branches, although one of them was weakly supported. Our results suggest that some past taxonomic proposals have low phylogenetic support and should no longer be used, e.g., based on their scattered positions in the phylogenetic reconstruction, several infraspecific taxa appear unrelated to the typical form of the species in which they had been placed. We present a phylogeny‐informed infrageneric classification of the genus Eriosyce, and new combinations are proposed to update the nomenclature of species and sections.